Sedrata : l’élaboration d’un lieu de mémoire - Cyrille Aillet (Université de Provence, 2012)
Almost entirely covered by sand, the archeological site of Sedrata, at about 10 kms south from Wargla, can be considered presently as a real lieu de mémoire for North African Ibadism. Every year a kind of pilgrimage is organised there, with the participation of Ibadi North African communities but also with an increasing variety of other visitors. This article will not deal with the history of Sedrata itself, excavated by the Swiss archeologist Marguerite van Berchem between 1950 and 1955, but rather with the function played by this place in the historical memory and imaginary of Algeria from the colonial era to nowadays. Sedrata was discovered and first interpreted during the great wave of exploring travels launched throughout the Sahara at the end of the 19th c. The academical appropriation of Sedrata began only in the 20th c. and displayed ethnicist and culturalist models for the interpretation of the archeological remains and decorative stuccos. A special mention of M. van Berchem’s investigations must be made for their key role in the integration of Sedrata into the Algerian national patrimony. In a very different way, the White Father J. Lethielleux contributed to the last developments in the forgery of the myth by his writings where local traditions are confusingly entangled with historical reports. Finally, we will also observe how local associations got involved with the protection of the site and the promotion of the pilgrimage.